Lithuanian national standards for the quality of palliative care - Šeškevičius, Arvydas (Slauga. Mokslas ir praktika, 2021)
A standard is a normative document that is prepared, adopted, and approved by competent organisations, sets norms, requirements, rules suitable for multiple use, general principles, or characteristics, and is intended to introduce optimal procedures in a certain field. Standards used in medicine set strict boundaries and clear indicators of how to meet a patient’s needs. They define how everything has to be organised to provide quality services. In addition, standards also define accessible, timely, equitable, complete, effective, reliable, and safe healthcare that meets quality requirements and is provided in the areas of disease prevention, diagnostics, treatment, nursing, and rehabilitation. The quality policy covers professional and administrative services. Lithuanian national standards for the quality of palliative care are designed to ensure appropriate and highquality palliative care services and to improve and develop them in order to meet the expectations of patients and their relatives. Quality standards contribute to the preparation and implementation of the strategy for the development the healthcare at the national level, the setting of health priorities and goals, and national coordination of personal healthcare services. In addition, they may serve as reference for the Ministry of Health. Quality standards have indisputable benefits for palliative care institutions as they help optimise the internal structure of operations, improve the process of the activity and work organisation, clearly define the powers of each employee, increase employee motivation and responsibility, improve the internal discipline and staff interaction at palliative care institutions, reduce errors, and improve working conditions, thus helping an organisation become an integrated system that ensures the provision of quality services to patients and their relatives. Individual chapters of the quality standards set out the principles, indicators, and requirements of palliative care, which together form an integrated system of quality. Interacting principles include the availability, goals, and continuity of palliative care, safety and infection control, medical measures, ethics, values and the expression of spirituality, and a multidisciplinary team focused on the patients and their loved ones. These principles and indicators ensure high professionalism, minimal risk to patients, and more effective improvement of healthcare services. For an objective evaluation of the effectiveness of palliative services, standardised scales and questionnaires are provided in the appendix. Many European countries have their own national quality standards for palliative care, which are revised every few years. Lithuanian quality standards for palliative care are the first document regulating the quality of palliative care in our country. The managing bodies of palliative care institutions, by demonstrating leadership to realise their vision, mission, and strategic directions, understanding quality as a core value and basis for action as well as an unconditional commitment to themselves and the patients, and by planning and implementing actions on possible risks, undertake to create a functioning system that implements, controls, and improves the institution’s processes in the areas of quality and patient safety. The book is aimed at service providers, health policy makers, all stakeholders, and decision makers. These first Lithuanian quality standards for palliative care have been adopted as national.